Регистрация
Войти
Алгебра

Решите уравнение (х+2)^3-х(3х+1)^2+(2х+1)(4х^2-2х+1) = 42

ОТВЕТЫ
(х+2)^3-х(3х+1)^2+(2х+1)(4х^2-2х+1)=42
x³+6x²+12x+8-x(9x²+6x+1)+(2x)³+1³=42
x³+8x³-9x³+6x²-6x²+12x-x+9=42
11x=33
x=3
(х+2)^3-х(3х+1)^2+(2х+1)(4х^2-2х+1)=42....
x^3+6x+12x+8-x(9x^2+6x+1)+(2x)^3+1^3=42
x^3+8x^3-9x^3+6x^2-6x^2+12x-x+9=42
11x=33
x=3
...^- это степень
268
Для написания вопросов необходимо войти в систему
Контакты
Обратная связь
support@sproshu.com
Спрошу
О проекте
Новым пользователям
Новым экспертам